Optimalisasi dan Produktivitas Alat Gali-Muat dan Alat Angkut pada Tambang Batu Granit PT Vitrama Properti di Desa Air Mesu, Kecamatan Pangkalan Baru, Kabupaten Bangka Tengah - Muhamad Nasuhi; E.P.S.B Taman Tono; Guskarnali Guskarnali (MINERAL, 2017)
Granite mining activity of PT Vitrama Properti is done by blasting system followed by work combination of one unit Excavator serve four units Dump Truck with a production target of 60.000 tonnes/month. The method of this research is quantitative descriptive to know achieving optimization and productivity Excavator-Dump Truck and efforts are needed to achieve the production target. The results of this research that digging and transport activities not run optimally seen from the low efficiency of work, which only reached 46,57% for digging activity and 40,51% material transport activities of the actual productivity of 29503,44 tons / month for Exacavator and 20754,72 tons / month for Dump Truck. Efforts are needed to achieve the production target is to make improvements circulation time of Dump Truck, increase the work efficiency of digging-transport activity and adding charging frequency to vessel Dump Truck.